(untitled) (Nigerian Journal of Technology, 2016)
The motor vehicle mechanics trainers’ are affected by the developments in the modern automobile technology (MAT) that brought about the use of auto scan tools for diagnosis and repair of modern vehicles in Nigeria. This study examined the capacity building needs among motor vehicle mechanics trainers in the use of auto scan tools. Three research questions and three null hypotheses guided the study. The study was carried out in three institutions where motor vehicle mechanics trade is offered as automobile technology or automobile education, three centers where auto scan tools are used for vehicle repairs and two technical colleges in Enugu state that offer motor vehicle mechanics (MVM) trade. The population of the study consisted of eighty three (83) MVM trainers, teachers and instructors. The instrument which was structured on two types of response scale (perceived importance and expressed performance) to elicit information on the use of auto scan tool for diagnosing some vehicle systems faults. Data collected were analyzed using the mean and the improvement needed index (INI) to answer the research questions. Then t- test statistic was used to test the null hypotheses at 0.05% level of significance. The study found out that MVM trainers need capacity building in the use of auto scan tools for vehicle systems diagnosis and repairs. The study recommended that workshop/seminars should be organized by centers like the National center for equipment maintenance and development, the National automotive council and so on to enable MVM trainers acquire the required skills to meet up with the training job facing them.